Histopathological Pattern of Testicular Biopsy in Male Azoospermics. - Mohammad Sajjad,Shabbir Hussian,Sajjad Ahmad, Mohammad Sajjad,Shabbir Hussian,Sajjad Ahmad (Journal of Rawalpindi Medical College, 2018)
Background: To find out the histological pattern of testicular biopsies in male azoospermics Methods: In this descriptive study testicular tru-cut biopsies (n=42), taken for the purpose of infertility, were included.Haematoxylin and Eosin staining as wells special stain like PAS where required was used for reporting. Exclusion criteria was insufficient, autolysed and unilateral testicular biopsy specimen. The slides were labeled and reported by Histopathologist as per WHO scoring criteria used for infertility purposes. Results: The age range was from 26 to 45 years with mean age of 28±17.22 years. The common age group was from 26 to 35 years (76.2%) followed by 36 to 45 years (23.8%). Azoospermic males of both Primary azzoseprmia was seen in 69.05% and secondary azoospermia was found in 30.95%. Normal spermatogenesis was noted in 28.57%,followed by spermatogenic arrest in 23.80%, reduced spermatogenesis in 21.42%, testicular atrophy in 18.04% and sertoli cell only in 7.14%. Conclusion: Normal or reduced spermatogenesis which were the commonest findings may suggest an obstruction in path of sperm motility, where surgical intervention may be curative.